Smith’s principle for congestion control in high-speed data networks - S. Mascolo (IEEE Transactions on Automatic Control, 2000)
In high-speed communication networks, large propagation delays could have an adverse impact on the stability of feedback control algorithms. In this paper, the classical control theory and Smith’s principle are exploited to design an algorithm for controlling "best effort" traffic in high-speed asynchronous transfer mode (ATM) networks. The designed algorithm guarantees the stability of network queues, along with the fair and full utilization of network links, in a realistic traffic scenario in which multiple available bit rate connections, with different propagation delays, share the network with high priority traffic.
Keywords: Communication system traffic control; Traffic control; Propagation delay; Stability; Algorithm design and analysis; Asynchronous transfer mode; Communication system control; Communication networks; Feedback control; Control theory